2022
DOI: 10.1038/s41598-022-18446-8
|View full text |Cite
|
Sign up to set email alerts
|

Single irrigation at the four-leaf stage in the spring optimizes winter wheat water consumption characteristics and water use efficiency

Abstract: Water scarcity is a key constraint to crop production in North China Plain (NCP), which produces the majority of the country’s winter wheat (Triticum aestivum L.). The objective of this three-year field study was to see whether and when irrigation one-time in spring improved grain productivity and water use efficiency. Four sets of irrigation were established at the 3-leaf visible stage (L3) and the L4, L5, and L6 stages. When irrigation time was postponed, the spike number, 1000-grain weight, and water consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Compared with the traditional crop growth stage, irrigation according to wheat leaf age has gradually become a new water-saving irrigation strategy that can accurately control wheat growth and yield formation. Our previous studies con rmed that single irrigation at spring 4 leaf age of winter wheat is an e cient water-saving irrigation technique (Bao et al 2022;Liu et al 2021). However, how to make up for the yield loss caused by single irrigation by changing agronomic practices needs further study.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Compared with the traditional crop growth stage, irrigation according to wheat leaf age has gradually become a new water-saving irrigation strategy that can accurately control wheat growth and yield formation. Our previous studies con rmed that single irrigation at spring 4 leaf age of winter wheat is an e cient water-saving irrigation technique (Bao et al 2022;Liu et al 2021). However, how to make up for the yield loss caused by single irrigation by changing agronomic practices needs further study.…”
Section: Introductionmentioning
confidence: 84%
“…Notably, irrigation at spring 4-leaf age is approximately one week later than irrigation at spring 3leaf age, resulting in a more balanced distribution of water consumption before and after the wheat jointing stage. Our prior research found that irrigation at spring 4-leaf stage achieved the highest yield and WUE with a single spring irrigation by increasing water consumption during the jointing-anthesis stage, reducing the duration of drought stress, and delaying leaf senescence (Bao et al 2022). Furthermore, it is essential to acknowledge the synergistic effects of water and nitrogen Liu et al 2022).…”
Section: Effects Of Irrigation and Nitrogen Application On Water And ...mentioning
confidence: 98%